A new species of Dalea (Fabaceae, Faboideae) from Jalisco, México - Castillón, Eduardo Estrada; Quintanilla, José Angel Villarreal (Phytotaxa, 2016)
In this paper we describe and illustrate Dalea jaliscana as a new species from Jalisco, Mexico, morphologically related to Dalea sericea.